The Rat Ovaries after U-74389G Process - Τsompos, C; Panoulis, C; Triantafyllou, A; Zografos, C G; Gerakis, E; Gerakis, S; Papalois, A (Free Radicals and Antioxidants)
Background: This study co-evaluated the 4 quoted histologic variables after U-74389G (L) administration. The calculation was based on the results of 2 preliminary studies, each one evaluating two respective histologic variables of Ovarian Epithelium Edema (OE), Oophoritis (OO), Ovarian Epithelium Karyorrhexis (OK), Ovarian Congestion (OC); in an induced ischemia reperfusion animal experiment. Furthermore, the Cytokine (TNFα) and the marker foroxidative stress Malondialdehyde (MDA) were also calculated. Materials and Methods: The 2 main experimental endpoints at which the OE, OO and OK, OC and TNFα, MDA scores were evaluated was the 60th reperfusion min (for the groups A and C) and the 120th reperfusion min (for the groups B and D). Specially, the groups A and B were processed without drugs, whereas the groups C and D after L administration. Results: The first preliminary study showed that L has a very significant recessing potency for OE and OC together (p-values=0.0157) within the “without lesions” alterations 0.1772727 [-0.3191054 - -0.03544]. The second preliminary study showed that L had a non-significant recessing potency for OK and OC within the “without lesions” grade 0.1772727 [-0.3716027 - +0.0170573] together (p-values=0.0726). These 2 studies were co-evaluated since they came from the same experimental setting. This study co-evaluated the combined diagnostic values of the four variables together. Separate calculations were performed for TNF-α and MDA scores. Conclusion: L administration significantly suppressed the 4 histologic variables within the “without lesions alterations” score 0.1772727 [-0.3208232 - -0.0337223] (p-value=0.0169), non-significantly reduced the TNF-α levels by 4.69% [+8.40%] (p-value=0.5749) and significantly reduced the MDA levels by 9.85%+2.66% (p-value=0.0005).
Keywords: Ischemia; U-74389G; Ovarian epithelium edema; Ovarian congestion; Ovarian epithelium karyorrhexis; Oophoritis; Reperfusion